2016
DOI: 10.3892/or.2016.5020
|View full text |Cite
|
Sign up to set email alerts
|

miR-194 is a negative regulator of GEF-H1 pathway in melanoma

Abstract: The incidence and associated mortality of melanoma continues to increase worldwide. At present, there is no curative therapy for advanced stage of melanoma. It is necessary to find new indicators of prognosis and therapeutic targets. Increasing evidence shows that miRNA can provide potential candidate biomarkers for melanoma and therapeutic targets. GEF-H1, a regulator of RhoA, as oncogenic driver in melanoma, promotes the growth and invasion of melanoma. miR-194 is a tumor-suppressor gene in multiple tumors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…In addition, we correlated the miRNA expression with patients' overall survival and could demonstrate that overall survival was significantly correlated with expression levels of hsa-miRNA-194-5p (p value <0.0001) although independence could not be demonstrated applying Cox regression analysis (p � 0.462; hazard ratio 1.469; 95% confidence interval 0.527-4.096). In accordance with our results, where higher levels of hsa-miRNA-194-5p corresponded to prolonged survival (97.67 months vs. 32.69 months), overexpression has been reported to inhibit cell proliferation and to act as a tumor suppressor in laryngeal SCC, prostate cancer, melanoma, bladder cancer, NSCLC, and clear cell renal carcinoma [83][84][85][86][87]. In addition, overexpression has been found to inhibit growth and proliferation in gastric cancer cell lines and esophageal squamous cell carcinoma [88,89].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, we correlated the miRNA expression with patients' overall survival and could demonstrate that overall survival was significantly correlated with expression levels of hsa-miRNA-194-5p (p value <0.0001) although independence could not be demonstrated applying Cox regression analysis (p � 0.462; hazard ratio 1.469; 95% confidence interval 0.527-4.096). In accordance with our results, where higher levels of hsa-miRNA-194-5p corresponded to prolonged survival (97.67 months vs. 32.69 months), overexpression has been reported to inhibit cell proliferation and to act as a tumor suppressor in laryngeal SCC, prostate cancer, melanoma, bladder cancer, NSCLC, and clear cell renal carcinoma [83][84][85][86][87]. In addition, overexpression has been found to inhibit growth and proliferation in gastric cancer cell lines and esophageal squamous cell carcinoma [88,89].…”
Section: Discussionsupporting
confidence: 92%
“…Studies have shown that miR-194 is downregulated in non-small cell lung cancer and clear cell renal cell carcinoma (ccRCC), and the reduced expression level is closely related to prognosis ( 18 , 19 ). Low expression levels of miR-194 was detected in ovarian cancer, colorectal cancer, melanoma and other tumors, and miR-194 can participate in the regulation of drug sensitivity and tumor growth through a series of signal pathways ( 20 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of miR-194 has been demonstrated in the origination and progression in certain varieties of cancer 22,23. To investigate the functional roles of miR-194 in CRC cell lines, we constructed miR-194 stably expressing SW480 cells.…”
Section: Discussionmentioning
confidence: 99%